ByzRev 06.2024.030: Mirela Ivanova, Inventing Slavonic.: Cultures of Writing between Rome and Constantinople (Oxford Studies in Byzantium). Oxford: Oxford University Press 2024. - Knoll, Vladislav (The Byzantine Review, 2025)
Mirela Ivanova, Inventing Slavonic. Cultures of Writing between Rome and Constantinople (Oxford Studies in Byzantium). Oxford: Oxford University Press 2024. 247 pp. – ISBN 978-0-19-889150-5